2002
DOI: 10.1126/science.1066161
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Anisotropy Below Slow- and Fast-Moving Plates: Paleoflow in the Upper Mantle?

Abstract: Upper mantle electrical conductivities can be explained by hydrogen diffusivity in hydrous olivine. Diffusivity enhances the conductivity of olivine anisotropically, making the a axis the most conductive of the three axes. Therefore, the hypothesis that plate motion induces lattice-preferred orientation of olivine can be tested with the use of long-period electromagnetic array measurements. Here, we compared electrical anisotropies below the slow-moving Fennoscandian and fast-moving Australian plates. The degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 18 publications
0
46
0
3
Order By: Relevance
“…Decomposed impedance strikes with a NE-SW trend to periods of $10,000 s lead Bahr and Simpson (2002) to suggest that the olivine in the upper mantle below southern Fennoscandia was strongly aligned despite the slow movement of the plate, thus inferring convective processes or fossil anisotropy were also contributing. However, forward modeling of the regional conductance map shows that crustal structure at least in the centralsouthern portion of the project area was sufficient to explain the great majority of the strikes and apparent anisotropy (Korja et al, 2002b;Lahti et al, 2005) (Figure 14).…”
Section: Fossil Transpressional Regimesmentioning
confidence: 96%
“…Decomposed impedance strikes with a NE-SW trend to periods of $10,000 s lead Bahr and Simpson (2002) to suggest that the olivine in the upper mantle below southern Fennoscandia was strongly aligned despite the slow movement of the plate, thus inferring convective processes or fossil anisotropy were also contributing. However, forward modeling of the regional conductance map shows that crustal structure at least in the centralsouthern portion of the project area was sufficient to explain the great majority of the strikes and apparent anisotropy (Korja et al, 2002b;Lahti et al, 2005) (Figure 14).…”
Section: Fossil Transpressional Regimesmentioning
confidence: 96%
“…Others have now made similar interpretations elsewhere in Canada and worldwide (Boerner et al 1999;Simpson 2001;Bahr and Simpson 2002;Hamilton et al 2006;Padilha et al 2006), although some of these interpretations are coming under closer scrutiny (Lahti et al 2005;Nieuwenhuis et al 2013). Also pioneered in Canada, and fully consistent with the multidisciplinary ethos of Lithoprobe, are qualitative comparisons between electrical and seismic anisotropy, with the first being the key publication by Ji et al (1996) in which the obliquity between the seismic and electrical anisotropy directions was interpreted as an indicator of mantle ductile shearing.…”
Section: Results With Global Consequencesmentioning
confidence: 81%
“…This is shown in Hamilton et al (2006) for South Africa, Miensopust et al (2011) for Botswana, and Adetunji et al (2014) for Ontario. An example of the dangers in using period as a proxy for depth is the interpreted imaging of the asthenospheric flow direction beneath Scandinavia from MT phases at a period of 2049 s by Bahr and Simpson (2002), whereas these long-period MT phase anisotropy effects were shown to be due to crustal artefacts by Lahti et al (2005). In addition, if there is significant difference in the resistivity in orthogonal lateral directions, due to either extrinsic (structure) or intrinsic (grain) anisotropy, the two different modes of MT will sample different depths at the same period (Jones 2006).…”
Section: Depth Of Penetrationmentioning
confidence: 99%
“…In a recent paper, Simpson (2013) showed that electrical anisotropy generated by hydrogen diffusivity in aligned olivine at mantle depth has an anisotropy factor of \4.5. Therefore, in other cases where much stronger electrical anisotropy in the mantle has been inferred from magnetotelluric models (e.g., Bahr and Simpson 2002;Gatzemeier and Moorkamp 2005), the anisotropy needs to be explained by other mechanisms, or isotropic heterogeneities have to be considered to explain the data (e.g., Korja et al 2002). Caricchi et al (2011) showed that anisotropy of electrical conductivity can be generated by interconnected melt channels in the spreading direction and low melt connectivity in the ridge parallel direction.…”
Section: Mantle Flow and Anisotropymentioning
confidence: 97%
“…Electrical anisotropy at lower crustal and upper mantle depths has been inferred from MT studies and been related to mantle flow (Simpson 2001;Bahr and Simpson 2002;Gatzemeier and Moorkamp 2005). One explanation for the anisotropy is the alignment of olivine crystals with respect to plate movement (lattice-preferred alignment).…”
Section: Mantle Flow and Anisotropymentioning
confidence: 99%